Predictors of Negative Sentinel Lymph Node Biopsy Results in Early Breast Cancer: a Retrospective Cohort Study - Naz, Saman; Javed, Ayesha; Naqvi, Syeda Rifaat; Saleema, Aqsa; Jabeen, Zohra; Naqvi, Syeda Saima Qamar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To identify clinicopathologic predictors of negative sentinel lymph node biopsy (SLNBx) in clinically node-negative breast cancer patients at a tertiary center in Pakistan.Study Design: Retrospective cohort study. Place and Duration of Study: Breast Surgery Department, Combined Military Hospital Rawalpindi, Pakistan, from Jan to Dec 2024. Methodology: Women with early-stage, clinically node-negative invasive breast cancer undergoing SLNBx were included. Data on tumor size, grade, receptor profile, Ki-67, comorbidities, and family history were analyzed. Chi square test was applied and p-value of ≤ 0.05 was considered as statistically significant. Results: Of 186 patients, 142 had complete data; 120 (84.5%) had negative SLNBx. There was a statistically significant association found between SLN and Menopause (p < 0.001), diabetes (p < 0.001), hypertension (p < 0.001), family history (p= 0.026), tumor grade (p < 0.001) and histology (p = 0.005). . Conclusion: A negative family history was the only independent predictor of SLNBx outcome. The high rate of pathologic node negativity supports selective de-escalation of axillary surgery in this subgroup.